COVID -19: The pandemic that has stopped the world for the first time - Ahumada, Oscar (2020)
In December 2019, a new virus appeared in Wuhan (China), SARS-CoV-2, the origin of the disease called COVID-19 that has currently caused a pandemic that devastates the planet. Globally, the scientific community is dedicating all its efforts to understand the virus, the disease and to find solutions that will lead the world out of this nightmare. This article reviews the data on the evolution of the disease, describes the biological processes that cause the major part of the deaths, and discusses the treatments used to mitigate the disease. In addition, and taking into account that it is a viral disease, the status of the only possible solutions are described; which are the discovery of a potential drug, the development of a vaccine, and the achievement herd immunity. Likewise, we present a simple mathematical model of the growth and decay of the number of cases. This document is written when the number of cases and deaths worldwide are still in a growth phase, therefore this document will be partial and only data published up to the date of writing this article will be collected (07/20/2020). It is possible that in the near future there will be new research that may make some of the information mentioned here obsolete, however, this text will allow the reader to create a slight image of the situation in July 2020.